PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA KABUPATEN PATI - Rovinda, Prita Sabillia; Syarifuddin, Syarifuddin (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
This study aims to determine, analyze, and examine the effect of work discipline and work motivation on employee performance. This research was conducted at the Office of Youth, Sports and Tourism, Pati Regency. The research method used in this study is a quantitative method. The sample used is a saturated sample, with a total of 38 respondents. Data collection techniques used are interviews, questionnaires, literature study. The data processing in this study used the SPSS 23 (Statical Package for the Social Sciences) software application. The data analysis techniques used were descriptive analysis and multiple linear regression analysis. Based on the results of descriptive analysis, work discipline is included in the good category, as well as work motivation is included in the good category and employee performance is included in the good category. Based on the results of this study indicate that work discipline and work motivation partially and simultaneously affect the performance of employees at the Office of Youth, Sports and Tourism, Pati Regency.